2007
DOI: 10.1371/journal.pgen.0030064
|View full text |Cite
|
Sign up to set email alerts
|

PPAR gamma 2 Prevents Lipotoxicity by Controlling Adipose Tissue Expandability and Peripheral Lipid Metabolism

Abstract: Peroxisome proliferator activated receptor gamma 2 (PPARg2) is the nutritionally regulated isoform of PPARg. Ablation of PPARg2 in the ob/ob background, PPARg2−/− Lepob/Lepob (POKO mouse), resulted in decreased fat mass, severe insulin resistance, β-cell failure, and dyslipidaemia. Our results indicate that the PPARg2 isoform plays an important role, mediating adipose tissue expansion in response to positive energy balance. Lipidomic analyses suggest that PPARg2 plays an important antilipotoxic role when induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
304
1
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 374 publications
(340 citation statements)
references
References 62 publications
23
304
1
9
Order By: Relevance
“…Since some relatively lean individuals are insulin resistant, whereas some very obese individuals are not, it was proposed that the maximal capacity for AT to expand is an individualize trait, perhaps determined by genetic background (Virtue and Vidal-Puig 2010). Moreover, rodent studies reported that mouse models on the ob/ob background with reduced capacity for ATE (due to partial lack of peroxisome proliferator-activated receptor gamma (PPARγ) function) presented reduced insulin sensitivity in comparison to the very obese ob/ob mice (Virtue and VidalPuig 2010;Medina-Gomez et al 2007). Spalding et al (2008) showed that adipocyte number remains constant in adulthood for both lean and obese individuals, and the difference in cell number between lean and obese is established during childhood and adolescence (Spalding et al 2008).…”
Section: Adipose Tissue Expansionmentioning
confidence: 99%
“…Since some relatively lean individuals are insulin resistant, whereas some very obese individuals are not, it was proposed that the maximal capacity for AT to expand is an individualize trait, perhaps determined by genetic background (Virtue and Vidal-Puig 2010). Moreover, rodent studies reported that mouse models on the ob/ob background with reduced capacity for ATE (due to partial lack of peroxisome proliferator-activated receptor gamma (PPARγ) function) presented reduced insulin sensitivity in comparison to the very obese ob/ob mice (Virtue and VidalPuig 2010;Medina-Gomez et al 2007). Spalding et al (2008) showed that adipocyte number remains constant in adulthood for both lean and obese individuals, and the difference in cell number between lean and obese is established during childhood and adolescence (Spalding et al 2008).…”
Section: Adipose Tissue Expansionmentioning
confidence: 99%
“…Chow-fed wild-type (WT), obese/obese knockout (ob/ob), Pparg-knockout (PpargKO), and ob/ob/PpargKO (POKO) male mice were generated on a mixed background as previously described [27] and epididymal AT was collected from groups at 4 and 16 weeks of age.…”
Section: Effects Of Pparγ Agonistsmentioning
confidence: 99%
“…It has been demonstrated that knockdown of a key adipogenic gene, PPARγ-2 in the ob/ob mouse model promoted decreased fat mass accompanied by severe IR, β-cell failure and dyslipidaemia compared with control mice (68) . Consistently, ob/ob mice overexpressing adiponectin, i.e.…”
Section: Adipogenesismentioning
confidence: 99%